2018
DOI: 10.1245/s10434-018-6623-2
|View full text |Cite|
|
Sign up to set email alerts
|

Phase 2 Open-Label Trial Investigating Percutaneous Laser Ablation for Treatment of Early-Stage Breast Cancer: MRI, Pathology, and Outcome Correlations

Abstract: BackgroundAn institutional review board-approved, multicenter clinical trial was designed to determine the efficacy and outcome of percutaneous laser ablation (PLA) in the treatment of invasive ductal breast carcinoma (IDC). Post-ablation magnetic resonance imaging (MRI) was compared with surgical pathology in evaluation of residual post-ablation IDC and ductal carcinoma in situ.MethodsPatients with a single focus of IDC 20 mm or smaller by pre-ablation MRI were treated with PLA. The patients underwent a 28-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…MRI is a sensitive image for diagnosis of the breast lesion (24). It has been used to predict tissue damage after BC ablation, and previous studies suggested MRI was suitable for long-term follow-up of ablation of BC with a NPV of 92.2-97.7% (25)(26)(27). MRI evaluated the efficacy of MWA with the NPV of 100% and specificity of 95.8% in our study.…”
Section: Discussionmentioning
confidence: 67%
“…MRI is a sensitive image for diagnosis of the breast lesion (24). It has been used to predict tissue damage after BC ablation, and previous studies suggested MRI was suitable for long-term follow-up of ablation of BC with a NPV of 92.2-97.7% (25)(26)(27). MRI evaluated the efficacy of MWA with the NPV of 100% and specificity of 95.8% in our study.…”
Section: Discussionmentioning
confidence: 67%
“…Imaging Techniques. MRI had a higher negative predictive value than US and mammography, respectively 92%, 89%, and 75% in 1 study, 17 and was not reported in other studies.…”
Section: Laser Ablationmentioning
confidence: 58%
“…In none of the studies the patient or physician was blinded, and in only 3 studies the pathology review was done by central review or by at least 2 independent pathologists. [17][18][19] A sample size calculation or estimation was given in only 5 studies 11 , 20-24 (Appendix D).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…[1,2] With the widespread availability of laser therapy devices in clinics, PTT attracts increasing interests of clinicians and patients due to its promising potential for effective treatment and minimized side effects. [3][4][5] However, advance of PTT for adoption in clinical cancer treatment is photosensitizers are NP size and surface chemistry. The NPs must be small so that they can be injected into the bloodstream, delivered to the tumor sites, and excreted through the renal and hepatic systems.…”
Section: Introductionmentioning
confidence: 99%